Penguatan Identitas Visual UMKM Abon Dua Saudara melalui Kegiatan Desain Spanduk - Aditya Bagas Pratama; Dwi Remawati; Retno Tri Vulandari; Kumaratih Sandradewi; Bramasto Wiryawan Yudanto (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
The rapid development of technology in the modern era requires micro, small, and medium enterprises (MSMEs) to adapt in order to remain competitive, particularly in the area of marketing and information dissemination. Abon Dua Saudara MSME, which has operated for over twenty years in the food processing sector, faces challenges related to limited promotional media, resulting in low public awareness of its products. This community service activity aims to strengthen the visual identity of Abon Dua Saudara MSME through the design and development of promotional banners using CorelDraw. The method employed in this program includes needs assessment, design training, and direct assistance in creating effective and visually appealing banners. The activity focuses on improving participants’ skills in utilizing digital design tools to produce promotional media that are informative, attractive, and aligned with the business identity. The results of this program indicate an improvement in the MSME’s capability to create independent promotional materials, as well as an enhanced visual identity that supports broader market reach. In conclusion, the implementation of banner design activities contributes positively to strengthening the branding and promotional effectiveness of Abon Dua Saudara MSME. This initiative is expected to increase public awareness and support the sustainability and growth of the business.